Organizational Behaviour and Human Resource Management A Guide to a Specialized MBA Course (Management and Industrial Engineering,, 2018)
This book focuses on strategic and operational human resources, giving the reader the core curriculum of subjects usually presented in an MBA program specialized in organizational behaviour and human resource management. The topics covered can be applied to a variety of real world business situations. This book aims to contribute to the growh and development of individuals in a competitive and global economy, by covering the latest developments in the field of human resources management. Innovative practices and theories as well as the current policies and practices of HRM are described in this book.